Motives for Male and Female University Students Engaging in Physical Exercise - Raul Josue Najera; Fernando Mondaca; Carolina Jimenez; Miguel Conchas; Susana Ivonne Aguirre; Yunuen Rangel; Ma. Concepcion Soto (European Scientific Journal, ESJ, 2019)
This paper focuses on comparing the motives for male and female Mexican university students engaging in physical exercise. The sample consisted of 455 participants; 237 women and 218 men with a mean age of 20.07 years (SD = 2.04) and 21.50 years (SD = 2.38) respectively. The approach adopted for this research was quantitative with a survey like descriptive design. Results from the multivariate analysis of variance, followed up by univariate analysis of variance, show that men exhibit a better motivational profile to engage in physical exercise. The encountered differences among female and male university students with respect to their motives in performing physical exercise suggest that when designing any type of interventionwith the goal of improving motivational profiles, it is necessary to consider the variable gender. Future research should replicate these results in larger samples.